2017
DOI: 10.1177/0886260517709799
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Bullying Victimization in Four Low-Resource Countries

Abstract: Bullying is one of the most common forms of aggression experienced by school-aged youth, yet research is sparse in low- and middle-income countries (LMIC) where cultural and contextual factors may influence victimization dynamics. We aimed to examine correlates of victimization and the prevalence of specific victimizing behaviors among youth in four LMIC. Data were included from 3,536 youth collected as part of the ongoing Young Lives Study cohorts in Ethiopia, India (Andhra Pradesh), Peru, and Vietnam who rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 40 publications
2
28
1
1
Order By: Relevance
“…This therefore makes depressed students targets of bullying. This finding is consistent with previous works among students which found psychological distress, social isolation and loneliness to be significantly associated with bullying victimization [813].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This therefore makes depressed students targets of bullying. This finding is consistent with previous works among students which found psychological distress, social isolation and loneliness to be significantly associated with bullying victimization [813].…”
Section: Discussionsupporting
confidence: 93%
“…Due to the dearth of research on bullying victimisation in developing countries, there remains a considerable gap in research that needs to be filled to provide an understanding into the scope and nature of the psychological effects of bullying victimisation as the findings in western countries may not necessarily be applied to the Ghanaian context. It has also been suggested that context and culture influences different patterns of victimization experiences among adolescents and young adults [13]. With no anti-bullying policy in place within Ghanaian schools in addition to the high prevalence of bullying reported among adolescents [1], there is therefore the need for a contextually relevant study to explore the various psychological distress that may be associated with bullying victimisation.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying victimization-repeated exposure to negative actions over time by one or more peers in the context of a power imbalance-is the most common type of school violence and is a major source of victimization among children and adolescents. 1,2 Across countries, there are considerable variations in rates of bullying victimization-ranging from as low as 5% to as high as 70%. 1 While the reasons for these variations are not entirely clear, they have been attributed to cultural factors 3 and social inequalities, where adolescents living in countries with wide socioeconomic disparities were found to be at higher risk of being bullied.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Across countries, there are considerable variations in rates of bullying victimization-ranging from as low as 5% to as high as 70%. 1 While the reasons for these variations are not entirely clear, they have been attributed to cultural factors 3 and social inequalities, where adolescents living in countries with wide socioeconomic disparities were found to be at higher risk of being bullied. 4 In Malaysia, the Global School-Based Student Health Survey (GSHS) conducted in 2012 reported that 17.9% of school-going adolescents aged 13 to 17 years were bullied at least once in the past 30 days, 5 although associated factors were not examined.…”
Section: Introductionmentioning
confidence: 99%
“…reported the prevalence and correlates of victimization among low-resource countries; the highest prevalence of victimization was reported from Peru (61.5%) followed by India (56.4%), Vietnam (38.6%), and Ethiopia (27.4%). [ 32 ] Skrzypiec et al . reported the following prevalence rates of victimization: the Philippines: 37.1%; Indonesia: 21.2%; and Taiwan: 5.4%.…”
Section: Discussionmentioning
confidence: 99%